PUTRI DUYUNG DALAM CORAK SUREALIS - Zolla Firmalia Rossa; Yasrul Sami (Serupa The Journal of Art Education, 2021)
This artworks made for visualize problems in women life and wish they can realize that it is important to increase their self-care. Also, this artworks hope that people could be more aware about problems they got as part of the society. The methods used in this final works are: 1) preparation stage, 2) Elaboration stage, 3) Synthesis stage, 4) The Concept Realization stage, and 5) Completion stage. So there are ten artworks visualizing mermaid in surrealism style, called “jantung Mata”, “Venus”, “Daughter of A Fish”, “Bunga Jiwa”, “Anchor”, “Shelter”, “Identity”, “How’s the Death Tasted?”, “Janin”, and “Standar Kecantikan,”.Keywords: Problems, Women, Artworks, Surrealism.